Pengaruh capital intensity dan corporate social responsibility terhadap agresivitas pajak dengan profitabilitas sebagai pemoderasi - Lodang Prananta Widya Sasana; Khairul Masyuri; I Gede Adi Indrawan; Jarno Carito (Jurnal Riset Pendidikan Ekonomi, 2022)
Taxes have an element of coercion resulting in many companies as taxpayers trying to practice tax resistance. Tax aggressiveness is one of the obstacles that occur in tax collection, resulting in reduced state treasury revenues. Tax aggressiveness can be done through a mechanism that is classified as tax evasion or tax avoidance. This study aims to determine and obtain empirical evidence of the effect of Capital Intensity and Corporate Social Responsibility on Tax Aggressiveness with Profitability as a moderator in LQ 45 companies listed on the Indonesia Stock Exchange (IDX). This research was conducted in the period 2014 – 2018 with a total research sample of 8 companies and using a purposive sampling method. This study uses descriptive statistical analysis techniques and multiple linear regression methods and tests on moderating variables with the Moderated Regression Analysis (MRA) method. The results of this study prove that Capital Intensity has a significant effect on Tax Aggressiveness, but Corporate Social Responsibility has no effect on Tax Aggressiveness. Meanwhile, simultaneously, Capital Intensity and Corporate Social Responsibility have a significant effect on Tax Aggressiveness. In addition, the results of this study also prove that profitability cannot moderate the corporate social responsibility variable on tax aggressiveness.